2010
DOI: 10.1039/b925576a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide reactions with atomic lanthanide cations and their monoxides: gas-phase kinetics at room temperature

Abstract: Results of experimental investigations are reported for the gas-phase kinetics of chemical reactions between nitrogen dioxide (NO(2)) and 14 different atomic cations of the lanthanide series, Ln(+) (Ln = La-Lu, excluding Pm), and their monoxides, LnO(+). Measurements were taken with an inductively-coupled plasma/selected-ion flow tube (ICP/SIFT) tandem mass spectrometer in helium buffer-gas at a pressure of 0.35 +/- 0.01 Torr and at 295 +/- 2 K. The atomic lanthanide cations were produced at ca. 5500 K in an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…[16,17] It was found that neither CeO + nor PrO + react with O 2 or H 2 Ot oy ield the dioxide cations, [16,17] whereas both react with NO 2 to yield CeO 2 + and PrO 2 + according to reaction (2) where M = Ce or Pr. [18] MO…”
Section: Synthesis Of Mo 2 + + Cationsmentioning
confidence: 99%
“…[16,17] It was found that neither CeO + nor PrO + react with O 2 or H 2 Ot oy ield the dioxide cations, [16,17] whereas both react with NO 2 to yield CeO 2 + and PrO 2 + according to reaction (2) where M = Ce or Pr. [18] MO…”
Section: Synthesis Of Mo 2 + + Cationsmentioning
confidence: 99%
“…We have been unable to find data on the reactions with ScO + or ZrO + , while the Bohme group's 2010 paper on NO 2 reactions of atomic lanthanide cations 12 lists the products of LaO + with NO 2 as LaO 2 + and LaO(NO 2 ) + , not NO + , in contradiction with the claim that LaO + produces NO + .…”
Section: Impurity Analysesmentioning
confidence: 68%
“…57 The cationic LnO + species are easily formed in the gas phase reactions of bare Ln + cations with oxygen-donor atom molecules. 58 Generally, the lanthanide monoxides cannot be obtained at normal pressure but it is possible to achieve the synthesis under high pressure (from La to Sm) and to keep them in normal conditions in a metastable state. In the case of cerium monoxide the synthesis has to be made under moderate pressures only using as the starting oxide CeO 2 , slightly reduced by heating in forming gas.…”
Section: Methodsmentioning
confidence: 99%